Photosynthetic efficiency of sugar beet, depending on the levels of fertilizer and plant density in the conditions of the western forest-steppe - Тирусь, М. Л. (Scientific Progress & Innovations, 2018)
Photosynthesis is the main physiological process that results in the formation of plant dry matter. Up to 90-95% of the accumulation of the dry mass of the sugar beet harvest during photosynthesis occurs in the leaves. The highest yields and the best yields can be obtained only in crops that have an optimal leaf area and with an optimal course of its formation, will be ensured by the rational use of mineral nutrition elements. For many years, the debate continues on changing the direction of the density of the standing of sugar beet plants with increased soil fertility due to fertilization. Depending on the amount of fertilizer applied, plant density can be adjusted. In the conditions of the western forest-steppe, a research was conducted to study the effect of fertilizer norms and plant density on the indicators of sugar beet photosynthetic productivity. It has been established that the use of plant density of 120-130 thousand pieces per hectare with the norm of N300P225K350 created the best conditions for the formation and growth of leaves of sugar beet plants. The area of leaves as of August 15 was 28,600 square meters per hectare more compared to the control variant without mineral fertilizer, with the same density of standing. Thickening of sowing to 140-150 thousand pieces per hectare led to a decrease in leaf area by 2-2.6 thousand square meters per hectare. The optimal area of nutrition of sugar beet plants and the formation of the best assimilation apparatus of the leaf surface for densities of 120-130 thousand pieces per hectare at a rate of N300P225K350 determined high rates of photosynthesis productivity: photosynthetic potential was 1.46 million m2 days / ha and net photosynthesis producti-vity – 4.53 g dry substances per square meter of leaf surface per day. As a result of the correlation analysis, a strong relationship between fertilizer levels and the photosynthetic potential of sugar beet plants (r = 0.98) and a weak direct relationship between fertilizer levels and net photosynthetic productivity (r = 0.28) was established.